2006
DOI: 10.1108/01437730610709309
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in servant leadership: the roles of values and personality

Abstract: PurposeThe paper seeks to address the lack of empirical research on servant leadership by investigating relationships between servant leadership and four individual differences – values of empathy, integrity, and competence and the five‐factor model's personality factor of agreeableness.Design/methodology/approachDennis and Winston's servant leadership scale (a revision of Page and Wong's servant leadership instrument), Braithwaite and Law's Goal and Mode Values Inventories, Mayer and Davis' integrity scale, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 45 publications
3
91
0
Order By: Relevance
“…Thus, individuals high in agreeableness might see higher levels of interdependent selfconstrual, and consequently of democratic / transformational leadership style. Washington et al (2006) also previously related servant leadership with agreeableness. Finally, conscientiousness is likely to be related to independent self-construal, since it fosters selfreliance and persistence in ones' initiatives and current work (Kirkpatrick and Locke, 1991).…”
Section: Personality Traits and The Power -Self-construal -Leadershipmentioning
confidence: 88%
“…Thus, individuals high in agreeableness might see higher levels of interdependent selfconstrual, and consequently of democratic / transformational leadership style. Washington et al (2006) also previously related servant leadership with agreeableness. Finally, conscientiousness is likely to be related to independent self-construal, since it fosters selfreliance and persistence in ones' initiatives and current work (Kirkpatrick and Locke, 1991).…”
Section: Personality Traits and The Power -Self-construal -Leadershipmentioning
confidence: 88%
“…Joseph & Winston (2005) examined the relationship between employee perceptions of servant leadership and organizational trust, and reported a positive relationship with both trust in the leader as well as trust in one's organization. Washington et al (2006) examined the relationship between servant leadership and the leader's values of empathy, integrity, competence, and agreeableness, and reported that "followers' ratings of leaders' servant leadership were positively related to followers' ratings of leaders' values of empathy, integrity, and competence" (p. 700).…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Servant leaders are suggested to be able to engender trust in organisations and their leaders (Washington et al, 2006). To able to trust senior officers and to be able to make mistakes in order to learn can be important within future policing initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…(Herzberg, 1966). Washington et al (2006) and Parris and Peachey (2013) illustrate that servant leaders tend to have a genuine concern for others arguing that they build trust through honesty and integrity and gain credibility through people's confidence in their knowledge, skills and abilities. Facilitating trust and integrity can only benefit a constable starting out in his/her career as it is trust, integrity and honesty that they too must exude to the public as part of their role as a police constable.…”
Section: Servant Leadership (Sl)mentioning
confidence: 99%